Strength Training Decreases Inflammation and Increases Cognition and Physical Fitness in Older Women with Cognitive Impairment - Chupel, Matheus U.; Direito, Fábio; Furtado, Guilherme E.; Minuzzi, Luciéle G.; Pedrosa, Filipa M.; Colado, Juan C.; Ferreira, José P.; Filaire, Edith; Teixeira, Ana M. (Frontiers in Physiology, 2017)
Cognitive impairment that affects older adults is commonly associated with an inflammatory imbalance, resulting in decreased physical fitness. Exercise has been pointed to mitigate immunosenescence and cognitive impairment associated with aging, while increase in physical fitness. However, few studies explored the relationship between changes in cytokine concentration and improvement on cognition due to elastic band strength training. The aim of this study was to investigate the effects of strength training on pro-and anti-inflammatory cytokines, haematological markers and physical fitness of older women with cognitive impairment. Methods: Thirty-three women (82.7±5.7 years old) participated in the study and were divided in two groups: strength exercise training group (ST; n=16) and Control Group (CG; n=17) and were evaluated before and after 28 weeks of the exercise program. The CG did not undergo any type of exercise programs. Data for IL-10, TNF-α, IFN-γ, C-Reactive Protein (CRP), white blood counts (WBC), red blood counts (RBC), Mini Mental State Examination (MMSE) and physical fitness tests were analysed in both moments. Results: IL-10 increased in the ST group without changes in CG. TNF-α and CRP increased in the control group while no changes were observed for IFN-γ in both groups. Strength training decreased leukocyte and lymphocyte counts and increase haemoglobin, mean cell volume and mean cell haemoglobin concentration. The MMSE score increased in strength training group but remained unchanged in the control group. A correlation between the variation of granulocyte counts and the MMSE scores was also observed within the total sample. An improvement in physical fitness was observed with strength training. Conclusion: Resistance exercise promoted better anti-inflammatory balance and physical performance simultaneously with an increase in cognitive profile in older women with cognitive impairment.